Carbon stock in Pulau Pintu Gedong mangrove forest, Malaysia / Mysha Farzana Peuny - Mysha Farzana , Peuny (2021)
Mangrove forests are regarded as the most significant carbon (C) sink in the tropics. They could play an important role in tackling climate change mitigation by reducing deforestation in the environmental, social, and economic sphere. The aims of the present study were to assess the species composition, phytosociological conditions and the ecosystem carbon stock in the tidal gradient of mangrove forest in Pulau Pintu Gedong in the west coast of Peninsular Malaysia. Blue Carbon stock was quantified in soil, downed wood and trees, saplings and seedlings components. The mean ecosystem carbon stock was about 783.58 ± 135.93 Mg /ha at two stations (one is fringe mangrove, and another is interior mangrove). Soil organic carbon stock contributed the largest share with a mean value of 636.55±87.36 Mg/ha. Approximately 632349.06 Mg C were estimated for the study site covering total of 807 ha of mangrove forest area. The prospective carbon pool from two stations of mangrove range from 3228.50 to 2522.98 Mg of C